Uso de simulação hidráulica na tomada de decisão em redes de abastecimento de água - Martins, Matheus Rodrigues (2018)
Water is essential for the development of human life. Although sanitation services have been improving in Brazil, brazilian water networks still lose 36,3% of the water distributed to the population. These water losses may be composed of leakages, measurements errors and unauthorized usages, and can be identified or controlled both manually and automatically. An important variable to control the water losses is the pressure value on the water supply network. The NBR 12.218 (ABNT), updated in 2017, sets maximum and minimum pressure values for the service to be satisfactory. In order for these limits to be fulfilled, equipments such as pumps and pressure reducing valves can be used to prevent pressure from being too low or too high. Although the indiscriminate use of these equipments can result in high costs, both financially and energy-efficiently, its rational use can save energy and, combined with methods for water reutilization or rainwater utilization, a sustainable system can be achieved. This work presents a modeled hydraulic representation of a real water supply network, located in São Gabriel-RS, Brazil, as a decision-making helping tool. Two scenarios were simulated considering maximum and minimum consumption, and areas with water pressure and velocity above and below the limits allowed were identified. The network was then sectorized and some improvements were suggested, such as new equipments, pressure reducing valves and a pump, pipe diameter decreases and changes in the pump scheduling. Another two scenarios were simulated to evaluate the impact of water reutilization and rainwater utilization on the network. The use of a hydraulic simulation showed a clear identification of pressure zones in different operation situations, which allowed the creation of a list prioritizing the suggested equipments in an order that would benefit the water network thus helping the decision-making process.